THE EFFECT OF CULTURAL IDENTITY REPRESENTATION IN BRITISH LITERARY WORKS ON CROSS-CULTURAL UNDERSTANDING AMONG INDONESIAN STUDENTS - Royaat; Hidayati; Misla Geubrina; Petra Eklesia; Winanda Salvira (Universitas Harapan Medan, 2026)
This study aims to examine the effect of cultural identity representation in selected British literary works on the cross-cultural understanding of Indonesian undergraduate students. The research is motivated by the limited ability of students to interpret cultural identity represented in literary texts and to relate those representations to broader social and cultural contexts. A mixed-methods approach was employed by integrating qualitative literary analysis with quantitative investigation of students' responses. The participants consisted of twenty undergraduate students enrolled in an English Literature program who participated in a literature-based instructional intervention. Data were collected through literary text analysis, pre-test and post-test questionnaires, classroom observations, reflective journals, and semi-structured interviews. Qualitative data were analyzed using thematic analysis, while quantitative data were examined using descriptive and inferential statistical techniques. The findings indicate that prior to the intervention, students demonstrated a moderate level of cross-cultural understanding, with a mean pre-test score of 62.45. Following the implementation of literature-based learning activities, the participants showed noticeable improvement in recognizing cultural identity representation, appreciating cultural diversity, developing empathy, and strengthening intercultural communication skills. Qualitative findings further revealed that collaborative discussions, reflective reading, and critical literary analysis encouraged students to construct broader perspectives on cultural diversity and intercultural relationships. The study concludes that cultural identity representation in British literary works has a positive influence on Indonesian undergraduate students' cross-cultural understanding when supported by structured, reflective, and student-centered instructional strategies. These findings contribute to the advancement of literary studies, cultural studies, and intercultural communication while providing practical implications for the development of English literature curricula and literature-based intercultural learning in Indonesian higher education.